THE EFFECT OF SHORT-TERM DEBT AND INSTITUTIONAL OWNERSHIP STRUCTURE ON THE PERFORMANCE OF COMPANIES LISTED ON SHARIA STOCK INDEX OF 2016-2018 PERIOD - Olga Mardianita Afifa; Sylva Alif Rusmita (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The trade-off theory by Kraus and Litzenberg (1972) indicates that debt has its effect on firm performance. As well as agency theory stated by Jensen and Meckling (1976), showing an effect between ownership structure and manager’s works, hence agency cost could be minimized and firm performance could be maximized. Therefore, this paper identifies the effect of short-term debt and institutional ownership towards firm performance partially and simultaneously, choosing 51 companies of trade, services, and investment sector of Indonesia Sharia Stock Index during 2016-2018. Three variables: short-term debt to total assets, institutional ownership, and Tobin’s Q have been tested using data panel regression analysis. Partially, the results show a positive and significant effect between short-term debt and firm performance. However, institutional ownership does not show any effect on firm performance. Simultaneously, short-term debt and institutional ownership have a significant effect on firm performance.Keywords: capital structure, ownership structure, firm performanceREFFERENCE Ardianingsih, A., & Ardiyani, K. (2010). Analisis pengaruh struktur kepemilikan terhadap kinerja perusahaan. Jurnal Pena, 19(1), 97–109.Dawar, V. (2014). Agency theory, capital structure, and firm performance: some Indian evidence. Managerial Finance, 40(12), 1190-1206. https://doi.org/http://dx.doi.org/10.1108/MF-10-2013-0275.Fachrudin, K. A. (2011). Analisis pengaruh struktur modal, ukuran perusahaan, dan agency cost terhadap kinerja perusahaan. Jurnal Akuntansi dan Keuangan, 13(1), 37–46. https://doi.org/10.9744/jak.13.1.37-46Handoo, A., & Sharma, K. (2014). A Study on determinants of capital structure in India. IIMB Management Review, 26(3), 170–182. https://doi.org/10.1016/j.iimb.2014.07.009Harjito, D. A. (2011). Teori pecking order dan trade-off dalam analisis struktur modal di Bursa Efek Indonesia. Jurnal Siasat Bisnis, 15(2), 187–196. https://doi.org/10.20885/jsb.vol15.iss2.art3Kao, M. F., Hodgkinson, L., & Jaafar, A. (2019). Ownership structure, board of directors and firm performance: Evidence from Taiwan. Corporate Governance (Bingley), 19(1), 189–216. https://doi.org/10.1108/CG-04-2018-0144.Sriyana, Jaka. (2014). Metode regresi data panel (dilengkapi analisis kinerja bank syariah di Indonesia). Yogyakarta: Ekosiana.Sudiyatno, B., & Puspitasari, E. (2010). Tobin’s Q dan Altman Z-Score sebagai indikator pengukuran kinerja perusahaan. Kajian Akuntansi, 2(1), 9–21.Sugiarto. (2009). Struktur modal, struktur kepemilikan perusahaan, permasalahan keagenan & informasi asimetri. Yogyakarta: Graha Ilmu.Sugiyono. (2014). Statistika untuk penelitian. Bandung: Alfabeta.